The Bai Bithaman Ajil contract as a mode of Islamic financing facility: issues and dilemma / Wan Murshida Wan Hashim and Marhaini Hassan - Wan Hashim, Wan Murshida; Hassan, Marhaini (2011)
The Bai Bithaman Ajil contract which constitutes the most favourite form of transaction commonly practiced by the Islamic Banking in Malaysia has been criticized by many quarters in the last few years. The implementation of the Bai Bithaman Ajil contract as a form of financial instrument is apparently to be contrary to the Syariah principles, thus invalid and unenforceable. There have been various ruling of the court pertaining to the legal issues arise in the Bai-Bithaman Ajil contract but some of the issues still remain unresolved. This paper aims to discuss the legal issues of the Bai Bithaman Ajil contract which are deemed to be contrary to the Syariah. Furthermore, it also reviews the ruling of the court pertaining to the legal issues arising thereof.